Greening the technology in teaching and learning - Sathivelu, Muttamah; Mariyappan, Raman; Md Zan, Zainal (2020)
Dawning of the digital era has create awareness among researchers to advocate ways to reduce the adverse effects of ICT usage in the country. Though the National Green Technology policy of Malaysia is well fabricated, little is known on how the ICT usage is being monitored and greening the technology is advocated. Studies show that ICT sector contributes to a large amount of carbon dioxide in the atmosphere and finally becomes e-waste due the rate of obsolescence. Nevertheless, ICT infrastructures such as computers puts on an overwhelming pressure on the energy grid. However, greening the ICT can make a significant contribution in reducing carbon dioxide emission and minimize the adverse effects of this technology to the environment. In the Malaysian education system, tremendous actions have been taken to build a more competitive and innovative approach in teaching and learning environment to garner students with digital knowledge for future contribution to the economic development though little is being done in advocating green ICT. Conclusively, this paper will put forward ways to greening the technology used in teaching and learning by teachers.